Citizen Charter Analysis In Public Sector Agencies (Study On Military Court II-09 Bandung) - Asep Hidayat; Gilang Alwasilah; Indi Ramadantica; Irma Syifa Ladista (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Abstract Indonesia is a developing country in the process of becoming a developed country.one of the priorities in this process is to improve and enhance the public service sector. Improving the public service sector by making and enforcing a Public Service Declaration, which is a written statement containing obligations and promises. Which is a written statement containing obligations and promises in service standards.in service standards. So this research aims to open up further understanding of the role of the Charter / Service Pledge in public sector agencies, especially in the sector agencies, specifically in the Military Court II-09 Bandung. Approach used in is a qualitative approach with data collection in the form of interviews, observations, literature studies and data analysis techniques sampling (purposive sampling) (purposive sampling). The results of this study indicate that Public Service Announcement is in accordance with the standards of the implementation of the Military Court II-09 Bandung. Keywords: Public Sector Agencies, Service Charter/Mandate, Service Quality